Identifikasi Bahaya, Penilaian Risiko, dan Pengendalian Risiko di Pabrik Roti PT X - Caroline Taher; Kriswanto Widiawan (Jurnal Titra, 2023)
PT X is a company that has been producing kinds of bread. Over the past 3 years, there have been 30 to 35 work accidents every year. Until now the company does not have occupational health and safety management system. This final project aims to identify hazards, carry out risk assessments, and create risk control for hazards in the company's production area. After conducting research, in the production area there are 16 sub-activities with 17 potential hazards. The risk assessment resulted in a high risk rating of 4 potential hazards, significant risk rating of 10 potential hazards, and a moderate risk rating of 3 potential hazards. Risk control carried out is 9 controls with technical design, 11 administration, 9 personal protective equipment, and 1 substitution. This control has been validated by the company's implementation. If all of these controls are carried out, then the estimated risk rating is a significant risk rating of 1, a moderate risk rating of 7, and a low risk rating of 9. The implementation is carried out in the activity of chopping coconut and attaching the oven plug to the electrical installation.